2013
DOI: 10.1371/journal.pone.0077439
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Eye Movements on Magnetic Resonance Imaging

Abstract: ObjectivesEye movements are the physical expression of upper fetal brainstem function. Our aim was to identify and differentiate specific types of fetal eye movement patterns using dynamic MRI sequences. Their occurrence as well as the presence of conjugated eyeball motion and consistently parallel eyeball position was systematically analyzed.MethodsDynamic SSFP sequences were acquired in 72 singleton fetuses (17–40 GW, three age groups [17–23 GW, 24–32 GW, 33–40 GW]). Fetal eye movements were evaluated accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Four fetal eye movement patterns were initially characterized based on early ultrasound observations ( Birnholz, 1981 ): Type I eye movements were described as single, transient deviations consisting of a bulb deviation, and a slower return back to the resting position, single but prolonged eye movements as Type II, complex sequences of eye movements to different directions without periodicity as Type III, and repetitive nystagmoid eye movements as Type IV. Additionally splitting of Type I eye movements into Type Ia (fast deviation, slower reposition) and Type Ib (fast deviation, equally fast reposition) was based on eye movement observation during MRI measurements ( Woitek et al, 2013 ). It has already been shown that MRI sequences provide a valuable tool for visualizing and categorizing fetal eye movements ( Brémond-Gignac et al, 1997 ; Woitek et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four fetal eye movement patterns were initially characterized based on early ultrasound observations ( Birnholz, 1981 ): Type I eye movements were described as single, transient deviations consisting of a bulb deviation, and a slower return back to the resting position, single but prolonged eye movements as Type II, complex sequences of eye movements to different directions without periodicity as Type III, and repetitive nystagmoid eye movements as Type IV. Additionally splitting of Type I eye movements into Type Ia (fast deviation, slower reposition) and Type Ib (fast deviation, equally fast reposition) was based on eye movement observation during MRI measurements ( Woitek et al, 2013 ). It has already been shown that MRI sequences provide a valuable tool for visualizing and categorizing fetal eye movements ( Brémond-Gignac et al, 1997 ; Woitek et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally splitting of Type I eye movements into Type Ia (fast deviation, slower reposition) and Type Ib (fast deviation, equally fast reposition) was based on eye movement observation during MRI measurements ( Woitek et al, 2013 ). It has already been shown that MRI sequences provide a valuable tool for visualizing and categorizing fetal eye movements ( Brémond-Gignac et al, 1997 ; Woitek et al, 2013 ). While this method was initially developed to serve as an indicator for ocular development and as an indirect biomarker to detect malformations affecting the brainstem, our study investigates for the first time the networks responsible for the processing of eye movement in utero , enabling the purest form of a natural self induced stimulus, eye movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial expressions such as smiling movements, pouting, or scowling can be observed during the last trimester of pregnancy by means of 4D ultrasound recordings, but their early ontogeny is not yet known. Fetal eye movements are particularly interesting (Video S5, online supporting information): fast deviations with slower/faster reposition, single prolonged eye movements, complex sequences, and nystagmoid eye movements can be observed from 15 to 17 weeks onwards 27 . From about 30 weeks onwards, clusters of rapid eye movements can be observed 8 .…”
Section: Facial Expressions and Fetal Eye Movementsmentioning
confidence: 99%
“…Fetal eye movements are particularly interesting (Video S5, online supporting information): fast deviations with slower/faster reposition, single prolonged eye movements, complex sequences, and nystagmoid eye movements can be observed from 15 to 17 weeks onwards. 27 From about 30 weeks onwards, clusters of rapid eye movements can be observed. 8 The fetus also starts to display blinking by opening and closing eyelids at 23 to 26 weeks' gestation.…”
Section: Facial Expressions and Fetal Eye Movementsmentioning
confidence: 99%